If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Sen(2x) + sen(4x) = 0 Remove parenthesis around (2x) enS * 2x + sen(4x) = 0 Reorder the terms for easier multiplication: 2enS * x + sen(4x) = 0 Multiply enS * x 2enxS + sen(4x) = 0 Remove parenthesis around (4x) 2enxS + ens * 4x = 0 Reorder the terms for easier multiplication: 2enxS + 4ens * x = 0 Multiply ens * x 2enxS + 4ensx = 0 Reorder the terms: 4ensx + 2enxS = 0 Solving 4ensx + 2enxS = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2enx'. 2enx(2s + S) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'enx' equal to zero and attempt to solve: Simplifying enx = 0 Solving enx = 0 Move all terms containing e to the left, all other terms to the right. Simplifying enx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2s + S)' equal to zero and attempt to solve: Simplifying 2s + S = 0 Reorder the terms: S + 2s = 0 Solving S + 2s = 0 Move all terms containing e to the left, all other terms to the right. Add '-1S' to each side of the equation. S + -1S + 2s = 0 + -1S Combine like terms: S + -1S = 0 0 + 2s = 0 + -1S 2s = 0 + -1S Remove the zero: 2s = -1S Add '-2s' to each side of the equation. 2s + -2s = -1S + -2s Combine like terms: 2s + -2s = 0 0 = -1S + -2s Simplifying 0 = -1S + -2s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 47.1=29.7-0.2x | | -47(x-11)-34=10-12 | | 2m-28=9m | | 2-7k=-4(k+1)-3 | | 4(x-8)=2x+6-x | | 3z-19=123 | | 2[t-(2t+8)+6]=2(t+2) | | 5x(x+8)+5x(6-x)=9(12+x)-8(7-x) | | 7(-6)(5)= | | 4z^2+3z-1=0 | | 2x^2-3y=32 | | -(z+7)+(5z+1)=5(z+1) | | 5x-19=3x+6 | | 3x(x+3)=24 | | 27x=33 | | 100-50= | | 8cosx-3=0 | | F(-1)=3x^3-5x^2-2x-5 | | 5x-2=125 | | 3x-7i=3(3x-7u) | | 8n+32=4(7n-7) | | (3a^3)(5a^2)= | | 2h=-3g+52 | | 2-3ln(x+1)=8 | | 3-2*-4=w | | 4(x+6)=6(x-2)+3x-4 | | y=2x^2-12x-19 | | (2x-1)+2(2x+6)=4x-1 | | (2p+3)(2p-3)=(2p+10)(2p-10)-91p | | 3h+13h=20-2 | | 6x+7=3x+8 | | 2x+3(x-2)=4x-24+2x |